A Comparative Study of Impact of Education and Occupation on Customers' Perception of E-Banking Services of Public Sector Bank and P.rivate Sector Bank (with Special Reference to Gwalior District, Madhya Pradesh) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
E-Banking is the term used for new age banking system. It is also called as online banking. E Banking uses the internet as the delivery channel by which to conduct banking activity, for example,  transferring funds, paying bills, viewing checking and savings account balances, paying mortgages  and purchasing financial instruments and certificates of deposits. Online Banking is a result of  explored possibility to use internet application in one of the various domains of commerce. It is  difficult to infer whether the internet tool has been applied for convenience of bankers or for the  customers' convenience. But ultimately it contributes in increasing the efficiency of the banking  operation as well providing more convenience to customers. Thee-banking is believed to facilitate  customers transact from one corner of the country to another corner. But the customers carry  varied perception about e-banking services based on multiple factors. The present paper explores  the impact of education and occupation of a customer in shaping their perception about internet  banking in both Public Sector Bank and Private Sector Bank .
Keywords: Online Banking; Customers' Satisfaction; Customers' Perception; Public Sector Bank; Private Sector Bank